Subspecific Differentiation Events of Montane Stag Beetles (Coleoptera, Lucanidae) Endemic to Formosa Island - Tsai, Cheng-Lung (PLoS One, 2016)
Taxonomic debates have been carrying on for decades over Formosan stag beetles, which consist of a high proportion of endemic species and subspecies featuring morphological variations associated with local adaptation. With the influence of periodical Pleistocene glaciations and the presence of several mountain ranges, the genetic differentiation and taxonomic recognition, within this medium-size island, of two endemic subspecies for each of four montane stag beetles, i.e. Lucanus ogakii, L. kanoi, Prismognathus davidis, and Neolucanus doro, has been an appealing issue. Based on monophyletic lineages and population structure, possible divergent scenarios have been proposed to clarify the subspecific status for each of the above mentioned stag beetles. Phylogenetic inferences based on COI+16S rDNA+28S rDNA of 240 Formosan lucanids have confirmed most species are monophyletic groups; and the intraspecific (<2%) and interspecific (>2%) genetic distances of the two mitochondrial genes could be applied concordantly for taxonomic identification. On account of Bayesian-based species delimitation, geographic distribution, population structure, and sequence divergences, the subspecific status for L. ogakii, L. kanoi, and Pri. davidis are congruent with their geographic distribution in this island; and the calibration time based on the mitochondrial genes shows the subspecific split events occurred 0.7–1 million years ago. In addition, a more complicated scenario, i.e. genetic differentiation including introgression/hybridization events, might have occurred among L. ogakii, L. kanoi, and L. maculifemoratus. The geological effects of mountain hindrance accompanied by periodical glaciations could have been vital in leading to the geographical subspecific differentiation of these montane stag beetles.